DESIGN AND DEVELOPMENT OF A SIMPLE WIND-POWER ELECTRIC GENERATOR EQUIPMENT - JAJULI (NIM: 20207049), HOLID
Wind energy can be utilized to be electric energy through two stages of conversion. First, the kinetic energy of wind is converted into rotation mechanical energy by using rotating propeller, and then the rotating rotor is connected to the dynamo. Wind resources that are used in this research come from the fan with brand of Maspion JF-2101T and coast-wind. Research method is the experimental method and the type of wind turbine that used is Horizontal Axis Wind Turbine (HAWT). The used propeller is made from thin PVC pipes with the mass density of 1.662619 gram/cm3; it is made into the trapezoid, fan-less, rectangular, oval and wing shape with each length of 25 cm. In this research it is obtained that the shape of propeller affects the resulted power and efficiency. By taking a fixed value of resistance R = 118 ohm, the largest power and efficiency are obtained from the trapezoid shape propeller with 5 blades, the efficiency is 5.983%. This research can be applied to the learning process of research for junior and senior high school students as related to the physics topics among others: Faraday Law, Bernoulli Law, inertia torque, and rotation movement.